Analysis of Award – Winning Children’s Fiction During the Years 2009 - 2015 - LI, NINGMIN; สัตโยภาส, สนิท; พลมณี, ศรีวิไล (Ganesha Journal, 2019)
The objective of this research aimed to study about the fiction books for children that received award from the Basic Education Committee during the years 2009-2015, in part of the contents, languages characteristics and the value of books. The instrument of this study was a table of data analysis. 20 children fictions were analyzed and the results of this study were presented in the form of descriptive analysis. The result revealed that; 1) the contents of the fiction books for children the received award during the years 2009-2015 were about love and relationship in family, sharing with others, being honest, gratefulness, teaching to conserve nature and environment; 2) the languages characteristics, the books were written by using simple words and sentences that suitable for children ages 6-11 years, namely, using correct words according with grammar, short words, compact words, elegant words and using words to create emotions and feelings. It was easy to read and understand for children, and 3) the value of books, divided to 3 types as followed; 3.1) the value of creative, it made children have imagination, intelligence, though with consideration and conceal with moral thinking as well, 3.2) the value of emotion, it taught children how to understand themselves and positive thinking. Finally, 3.3) the value of society, it taught children how to work together, being good leader or follower and helping each other.